Quantitative Determination of Anticancer Drug Heptaplatin by HPLC - He, Xuefeng; Zhen, Ping; Chen, Xizhu; Yang, Shuiyan; Xie, Xiaotian; Liu, Weiping (Asian Journal of Chemistry, 2010)
A method for the direct determination of anticancer drug heptaplatin by HPLC has been described. Phenomenex ODS column (150 mm × 4.6 mm i.d., 5 μm) was used as the stationary phase and a mixture of methanol and water (40:60, v/v) as the mobile phase. The flow rate was 1.0 mL min-1, T = 40 ºC and the detection wavelength was 230 nm. Under these analytical conditions, the linear regression coefficient was found to be 0.9999, the average recovery exceeded 99.9 % with RSD 0.85 %. The method is accurate, reliable and rapid. It can be applied to the quality control of heptaplatin.